Bubble Window Product Quality Control with New Seven Tools Method (Case Study: PT X) - Anriady Miftahul Putra; Indro Prakoso (School of Industrial and System Engineering, Telkom University, 2021)
Quality control is needed to prevent material, time, and energy losses for the company PT. X. By doingquality control on bubble window production, it is expected to reduce the adverse impact on the company.PT. X itself is a company engaged in aircraft manufacturing. In producing each aircraft component, PT. Xrequires quality control to be able to guarantee the aircraft has good quality and meets the standards thathave been set. In bubble window production, defects are still found. Bubble window itself is one of thecomponents of the aircraft which is produced by PT. X. In an effort to reduce the number of defects thatoccur, quality control is carried out using the new seven tools method. From the processing results obtainedfive factors that cause defects in bubble window products at PT. X, namely the environment, humans,machines, methods, and materials. So three solutions are proposed,which are reviewing the operation of themachine, placing the SOP position in the work area, and periodic maintenance.